Effects of Shrinkage Reducing Agent and Expanded Cement on UHPC Fluidity, Mechanical Properties, and Shrinkage Performance. (22nd July 2021) - Wang, Tingyu; Gong, Jianqing; Chen, Bo; Gong, Xiao; Luo, Hongkui; Zhang, Yang; Qu, Zhigang
Abstract : The purpose of this study was to evaluate the effects of a shrinkage reducing agent (SRA) and Portland expanded cement (PEC) on the fluidity, mechanical properties, and shrinkage performance of ultrahigh-performance concrete (UHPC). The results indicated that the fluidity of the fresh UHPC mortar initially decreased and then increases along as a function of SRA dosage. When the dosage of SRA was 1%, the UHPC mortar fluidity was at its minimum. For dosages exceeding 1%, the additional water-binder ratio of the mortar increased, which in turn increased the UHPC fluidity. That is, the SRA delayed the cement hydration and increased the setting time, which is not conducive for early strength development of UHPC. As the SRA dosage was increased (i.e., 0%–2%), the autogenous shrinkage of UHPC decreased significantly such that even a small dosage of about 0.5% SRA was able to effectively reduce drying shrinkage. From the study results, it was also observed that PEC accelerated the loss of fluidity in the fresh UHPC and concurrently promoted the early strength development of UHPC. At 75% PEC content, the strength enhancement effects tended to be stable. This means that although the addition of PEC will potentially increase the autogenous shrinkage of UHPC, it has the positive effect of inhibiting drying shrinkage provided that the PEC dosage is controlled within the 25%–50% range. Furthermore, morphological analyses using a scanning electron microscope (SEM) indicated that an increase in the SRA dosage loosens the UHPC microstructure, with the formation of the hydration products remaining incomplete, thus ultimately causing the UHPC strength to decrease. Overall, the study findings indicated that 2% SRA and 25%–50% PEC can effectively reduce the shrinkage of UHPC and are, therefore, recommended as the optimum dosages.